The Efficacy of Physical Fitness Training on Dance Injury: A Systematic Review - Dang, Yanan; Chen, Ruoling; Koutedakis, Yannis; Wyon, Matthew Alexander (Sportverletzung · Sportschaden, 2024)
Greater levels of physical fitness have been linked to improved dance performance and decreased injury incidence. The aim was to review the efficacy of physical fitness training on dance injury. The electronic databases CINAHL, Cochrane Library, PubMed, Web of Science, MEDLINE, China National Knowledge Infrastructure were used to search peer-reviewed published articles in English or Chinese. Studies were scored using Strength of the Evidence for a Conclusion and a risk bias checklist. 10 studies met the inclusion criteria from an initial 2450 publications. These studies offered physical fitness training for professional (n = 3) and pre-professional dancers (n = 7), participant sample size ranged between 5 to 62, ages from 11 to 27 years, and most participants were females. Assessment scores were classified as Fair (n = 1), Limited (n = 7), and Expert Opinion Only (n = 2) and risk of bias scores ranged from 22.7–68.2 %. After physical fitness training, 80 % of studies reported significant benefits in injury rate, the time between injuries, pain intensity, pain severity, missed dance activities and injury count. This review suggests that physical fitness training could have a beneficial effect on injury incidence in dance. The evidence is limited by the current study methodologies.
Keywords: rehabilitation; prehabilitation; ballet; muscle strength